The magic mirror - Staniszewski, Anna; Pamintuan, Macky (New York : Scholastic Inc., 2019)
The Ice Princess's magic mirror is broken, one piece is missing, and without it the Enchanted Kingdom is locked in a terrible, unseasonable, heat wave (even the palace is melting); two children, Kara and Zed, are determined to help, but first they must figure out whether the break is the result of the sibling rivalry between the Ice Princess and her sister the Sun Princess--or did the monkey do it?
Accelerated Reader
Keywords: Magic mirrors -- Juvenile fiction; Magic -- Juvenile fiction; Princesses -- Juvenile fiction; Characters and characteristics in literature -- Juvenile fiction; Sisters -- Juvenile fiction; Sibling rivalry -- Juvenile fiction; Monkeys -- Juvenile fiction; Fantasy fiction